Analisis Prosedur Pemeriksaan CT Scan Abdomen Tiga Fase Pada Klinis Adenocarcinoma Colon Metastasis Hepar Di RSUP Persahabatan Jakarta Timur - Reski Ramadhani; I Putu Eka Juliantara; I Made Purwa Dharmita (Journal of Educational Innovation and Public Health, 2023)
Background: CT scans can be used as a supporting tool to evaluate various abnormalities and determine certain clinical conditions, one of which is that abdominal examination is used to make clinical diagnoses such as liver metastatic colon adenocarcinoma. Three-phase abdominal examination technique for clinical adenocarcinoma colon liver metastases carried out at Persahabatan Hospital using intravenous injection of contrast media without oral and rectal use with a delay time technique. Results: The three-phase abdominal CT scan examination procedure for clinical adenocarcinoma colon metastases to the liver was carried out using the Abdomen_3Phase protocol with a helical type scan with intravenous administration of contrast media which was sufficient to confirm the diagnosis with post-contrast scanning, namely in the arterial phase using a delay of 22-25 seconds, for the venous phase, that is 50-60 seconds, then for the equilibrium/delayed phase, that is 90-100 seconds from the beginning of the introduction of the contrast medium which is reconstructed into a 5 mm slice thickness sagittal and coronal section. A three-phase abdominal examination is carried out to evaluate abnormalities in the abdomen such as intra-abdominal masses so that it can differentiate between masses and metastases. Conclusion: The technique of inserting contrast media into a three-phase abdominal examination in clinical adenocarcinoma colon liver metastases at the radiology installation at Persahabatan Hospital, East Jakarta is carried out intravenously and is sufficient to confirm the patient's diagnosis. This is done because the focus is on assessing the liver, where the liver is a dense cavity. so that to assess abnormalities in the liver, contrast media can be injected intravenously, and for the condition of the colon, it can be assessed in general terms without going oral or rectal.